Sintesis dan Karakterisasi Nanopartikel Zn Menggunakan Kitosan Sebagai Reduktor - Astuti Amin; Sri Reski Ananda (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2020)
Zn nanoparticles is a material that is widely used in the pharmaceutical and cosmetic industry, as a sunscreen, skin whitening, and anti-aging. The aim of the research was to synthesize Zn nanoparticles using chitosan as a stabilizer by chemical reduction method and determine the effect of chitosan amount on the stability of Zn nanoparticles. This research, the raw material used is shrimp shell powder and then processed in several stages, eliminating proteins, demineralization, and deacetylation. Chitosan obtained is 22,8 % of shrimp shell powder, with a degree of deacetylation is 85 %. Chitosan was used to synthesize Zn nanoparticles as a reducing agent of Zn ions in the ZnO solution and was expected to be a stabilizer. The measurement using Atomic Absorption Spectroscopy (AAS) shows that the concentrate of Zn in solution synthesis result of 13,88 mg/l, based on the UV-Vis spectrophotometry obtained maximum wavelength of 355,71 nm and absorbance of 0,062, the shapes of the nanoparticles obtained tend to aggregate. Based on measurements by Particle Size Analyzer (PSA) which has been synthesized Zn nanoparticles have the average size of the particles in the sample is 213,41 nm.